GAMBARAN TEKANAN DARAH PRA DAN PASCA BERZIKIR PADA ANGGOTA MAJELIS ZIKIR AL-HIDAYAH PEKANBARU - Faradini "; Dani Rosdiana; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTDhikr (dzikrullah) means calling and saying the name of Allah with a tongue (oral) or the heart (qalbu). Dhikr can be meditation to induce relaxation response and can affects the autonomic nervous system responding to the blood pressure. The study was descriptive with cross-sectional design by measuring the blood pressure to know the profile of the blood pressure pre and post dhikr of Majelis Zikir Al-Hidayah Pekanbaru member. The data collection was primary data in 66 respondents who have a blood pressure >117/76 mmHg. The results showed that the mean blood pressure of all respondents pre and post dhikr were 138/83 mmHg and 134/81 mmHg (a difference of 4/2 mmHg). The mean decrease in systolic blood pressure and diastolic blood pressure is greatest among respondents in the age group 18-24 years (7/3 mmHg), male gender (7/2 mmHg), educated graduated from D1-D3 / PT (6 / 3 mmHg), worked as an employee (9/10 mmHg), had low body mass index (6/4 mmHg), strenuous physical activity (7/3 mmHg), smoked / ever smoked (6/3 mmHg), has a history of hypertension of family (10/2 mmHg), and has a moderate level of stress (5/4 mmHg). There is a decrease in blood pressure after dhikr done by member of Majelis Zikir Al-Hidayah Pekanbaru.Keywords: Dhikr, meditation, blood pressure